2009
DOI: 10.1007/s10822-009-9304-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative virtual screening and novelty detection for NMDA-GlycineB antagonists

Abstract: Identification of novel compound classes for a drug target is a challenging task for cheminformatics and drug design when considerable research has already been undertaken and many potent lead structures have been identified, which leaves limited unclaimed chemical space for innovation. We validated and successfully applied different state-of-the-art techniques for virtual screening (Bayesian machine learning, automated molecular docking, pharmacophore search, pharmacophore QSAR and shape analysis) of 4.6 mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…Our findings are in agreement with a recent study where NMDA receptor antagonists were selected from a library of 8.8 million compounds, applying different virtual screening methods i.e. 2D descriptor-based filtering, molecular docking, QSAR pharmacophore hypothesis and 3D shape search [26]. The best positive hits from each approach were further evaluated by in vitro tests.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings are in agreement with a recent study where NMDA receptor antagonists were selected from a library of 8.8 million compounds, applying different virtual screening methods i.e. 2D descriptor-based filtering, molecular docking, QSAR pharmacophore hypothesis and 3D shape search [26]. The best positive hits from each approach were further evaluated by in vitro tests.…”
Section: Discussionsupporting
confidence: 89%
“…The integrated use of docking and structureactivity relationship models to determine ligand, substrate, or inhibitor specificity has greatly advanced our understanding of the mechanism of receptors and drug transporters (Khandelwal et al, 2008;Krueger et al, 2009). To date, several combinations of structure-and/or ligand-based methods have been reported to characterize hPXR and activator interactions (Gao et al, 2007;Ekins et al, 2008;Khandelwal et al, 2008;Yasuda et al, 2008), but application of this strategy to Previous docking studies on hPXR indicated that directly using the "cutoff score" from docking programs was limited for prediction and classification of hPXR activators and nonactivators (Ekins et al, , 2009Khandelwal et al, 2008;Yasuda et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Krueger et al validated different techniques for virtual screening to identify potential competitive antagonists of the NMDA receptor glycine binding site located in the NR1 subunit [113]. Molecular docking, pharmacophore search, pharmacophore QSAR and Bayesian machine learning were used for virtual screening of 4.6 million chemicals.…”
Section: Structure-based Methods Docking Virtual Screening and Molementioning
confidence: 99%